A techno-economic and life cycle assessment for the production of green methanol from CO2: catalyst and process bottlenecks - Cordero-Lanzac, Tomás; Ramirez, Adrian; Navajas, Alberto; Gevers, Lieven; Brunalti, Sirio; Gandia, Luis M.; Aguayo, Andrés T.; Sarathy, S. Mani; Gascon, Jorge (Elsevier, 2022)
The success of catalytic schemes for the large-scale valorization of CO2 does not only depend on the development of active, selective and stable catalytic materials but also on the overall process design. Here we present a multidisciplinary study (from catalyst to plant and techno-economic/lifecycle analysis) for the production of green methanol from renewable H2 and CO2. We combine an in-depth kinetic analysis of one of the most promising recently reported methanol-synthesis catalysts (InCo) with a thorough process simulation and techno-economic assessment. We then perform a life cycle assessment of the simulated process to gauge the real environmental impact of green methanol production from CO2. Our results indicate that up to 1.75 ton of CO2 can be abated per ton of produced methanol only if renewable energy is used to run the process, while the sensitivity analysis suggest that either rock-bottom H2 prices (1.5 $ kg 1 ) or severe CO2 taxation (300 $ per ton) are needed for a profitable methanol plant. Besides, we herein highlight and analyze some critical bottlenecks of the process. Especial attention has been paid to the contribution of H2 to the overall plant costs, CH4 trace formation, and purity and costs of raw gases. In addition to providing important information for policy makers and industrialists, directions for catalyst (and therefore process) improvements are outlined.
Keywords: Metanol (Combustible); Hidrogenación de CO2; Diseño reactores; Análisis tecnoeconómico; Análisis de ciclo de vida; Ingeniería Química